Sustained hydrogel-based delivery of RNA interference nanocomplexes for gene knockdown - Ngarande, Ellen (Division of General Surgery, 2020)
Scaffold based delivery of RNA interference (RNAi) molecules such as free small interfering RNA (siRNA) and microRNA has recently begun to be employed towards treatment of diseases such as cancer, bone regeneration, muscular dystrophy and cardiovascular disease. Effective translation from bench side to clinical use of RNAi has been limited in part because upon systemic delivery the RNAi molecules are degraded by RNases and flushed by excretory organs causing an inefficient duration of gene silencing effect at target tissues. These challenges can potentially be minimised by delivering RNAi molecules via non-viral nanoparticle carriers encapsulated in biocompatible, biodegradable and injectable scaffolds such as hydrogels. Various scaffolds have been shown to aid in sustained localised delivery of RNAi molecules and improve gene silencing. This research focused on optimising and establishing such an RNAi hydrogel-siRNA-nanoparticle (hydrogel-nanocomplex) system for targeted and sustained gene knockdown both in vitro and in vivo using dendrimer and lipid based nanoparticles in combination with synthetic polyethylene glycol (PEG) and natural fibrin hydrogel scaffolds. Four siRNA nanocarriers were investigated for siRNA delivery, that is, fourth generation dendrimer nanoparticles poly(amidoamine) (D) and its modified version (MD) with PEG and a lipid 1, 2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE) molecule, commercial lipid based Lipofectamine® RNAiMax and Invivofectamine® 3.0 nanoparticles. D and MD achieved better RNase protection compared to lipid nanocomplexes though Invivofectamine® 3.0 nanocomplexes protected a small percentage of siRNA over 10 days. The MD nanoparticle displayed improved siRNA release and transfection efficacy compared to D but efficacy of the dendrimers was lower than the lipid particles. Four hydrogels that have not been investigated for RNAi were assessed for sustainability. Namely, hydrolytically and proteolytically degradable PEG-acrylate (PEGAC), proteolytically degradable PEG - vinyl sulfone (PEG-VS) hydrogels, unmodified fibrin and PEGylated fibrin hydrogel. The nanocomplex release rate in vitro from the various hydrogels showed minimal release from PEGylated hydrogels, burst release from unmodified fibrin and sustained release from PEGylated fibrin. Invivofectamine® 3.0 nanocomplexes retained efficacy optimally after release from PEGylated fibrin hence this hydrogel was utilised for downstream analysis. For in vivo sustained delivery to be effective, determination of hydrogel persistence in vivo was required. After injection in the mouse tibialis anterior (TA) muscle PEG-AC and PEGylated fibrin gels degraded within 2 days. The efficacy of the various nanocomplexes was assayed in a 3D assay that more closely resembled delivery in soft tissue. PEGylated fibrin containing nanocomplexes with cell death siRNA sequences was polymerised around a preformed PEGylated fibrin cell containing droplet. Invivofectamine® 3.0 nanocomplex consistently achieved the highest gene knockdown effect with no evidence of cytotoxicity whilst Lipofectamine® RNAiMax was ineffective. MD showed signs of cytotoxicity when delivered in a sustained fashion. Thus Invivofectamine® 3.0 nanocomplexes in PEGylated fibrin hydrogel were found to be the optimal gel-nanocomplex system to proceed to in vivo assessment. BALB/c GFP transgenic injected in their TA muscle with Invivofectamine® 3.0 nanocomplexes made with siRNA targeting GFP or myostatin (siGFP/siMSTN) in the presence or absence of PEGylated fibrin gel were analysed 7 days post treatment for siRNA retention and GFP and Mstn gene knockdown. Increased retention of siRNA after encapsulation in PEGylated fibrin was observed at 7 days. A non-significant reduction in GFP protein was seen for limbs injected with siGFP- fibrin after 7 days. A substantial and significant reduction in Mstn mRNA levels was elicited by delivery of siMstn–fibrin. Furthermore, only siMstn-fibrin resulted in significant increase in muscle mass. In this study, dendrimer based nanoparticles were found to effectively protect siRNA against RNases however lipid based nanocomplexes were the most efficacious at gene knockdown. The combination of Invivofectamine® 3.0 and PEGylated fibrin was shown to be the most effective in 3D assays and as an injectable controlled release scaffold into soft tissue suggesting that this approach has therapeutic potential.